Species Variability in Platelet and other Cellular Responsiveness to Thrombin Receptor-derived Peptides - Connolly, Thomas M; Condra, Cindra; Feng, Dong-Mei; Cook, Jacquelynn J; Stranieri, Maria T; Reilly, Christopher F; Nutt, Ruth F; Gould, Robert J (Thrombosis and Haemostasis, 1994)
The aggregation of platelets from a variety of animal species in response to thrombin receptor-derived activating peptides was evaluated. A series of 14-(SFLLRNPNDKYEPF), 7-(SFLLRNP-NH2), 6-(SFLLRN-HN2) or 5-(SFLLR-NH2) residue peptides, the structures of which were based on the deduced amino acid sequence of the human thrombin receptor, promoted full aggregation of platelets in plasma from humans, African Green and Rhesus monkeys, baboons and guinea pigs at 4-50 μM depending on the peptide used. Platelets in plasma from rabbit, dog, pig, and hamster underwent a shape change but failed to aggregate in response to these peptides over 3 log units of peptide up to 800 μM, despite being fully responsive to human thrombin. However, because the receptor peptides induced shape change in the platelets from these non-aggregating species, they apparently can activate some of the intracellular signaling system(s) usually initiated by thrombin in these platelets. In contrast, platelets from rats did not undergo shape change or aggregate in response to the peptides. A 7-residue receptor-derived peptide based on the deduced amino acid sequence of the clone of the hamster thrombin receptor (SFFLRNP-N2) was nearly as efficacious as the corresponding human receptor-derived 7-residue peptide to promote aggregation of human platelets. However, the hamster peptide could not promote aggregation of hamster platelets in plasma at up to 800 μM peptide, while a shape change response was elicited. Platelets from rats, rabbits and pigs also did not aggregate in response to this peptide derived from the hamster thrombin receptor, but all species except the rat underwent a shape change. Longer 17-residue peptides derived from the sequences of the hamster or mouse thrombin receptors elicited aggregation of human platelets but no aggregation of the hamster platelets. In contrast, the human 14- and 5-residue and the hamster 7-residue thrombin receptor-derived peptides promoted mitogenesis of CCL39 cells, a hamster fibroblast cell line. Finally, the human 6-residue thrombin receptor-derived peptide promoted contraction of normal and de-endothelialized canine coronary artery rings, despite having no pro-aggregatory effect on canine platelets. Taken together, these results demonstrate that the thrombin receptor-derived peptides are able to mimic many, but not all, of the activating effect of thrombin in different tissues from multiple species. The heterogeneity of responsiveness to these peptides should be taken into account in future experiments designed to elucidate the mechanism of thrombin stimulation of platelets and other cells.